(untitled) (Indian Journal of Arid Horticulture, 2025)
Studies on virus tolerant, citrus rootstock Cleopatra (Citrus reshnii Tanaka) were carried out by using nodal segments of seedlings as explants. The maximum survival of explants (90 per cent) and minimum time required to bud breaking (19.50 days) was recorde on BAP 0.5mgl’ + kinetin 0.5 mgl’. However, maximum number of shoot (7.30) was there on BAP 2.0 mgl’+ kinetin 1.0 mgl’ and maximum length shoot (2.40 cm) on BAP 0.5 mgl’ + kinetin 2.0 mgl". The maximum (90 per cent) survival of micro shoot for rooting and length of root (6.28 cm) were recorded on M S medium modified with NAA 0.5 mgl’+ IBA 0.5 mgl". The minimum time taken to root induction (22.00 days) was on NAA 0.5mgl + IBA 0.1 mgl’ and maximum number of root (5.60) was on NAA 0.5 mgl’ + IBA 1.0 mgl’. In-vitro propagated plantlets were successfully acclimatized by transferring then in pots containing a potting mixture of soil: perlite: vermiculite in equal proportion. Plantlets survival ofv90 per cent was observed in this mixture.